PEMANFAATAN DAUN KELOR (MORINGA OLEIFERA) SEBAGAI SUPERFOOD LOKAL UNTUK PERBAIKAN GIZI KELUARGA DAN PENCEGAHAN STUNTING - Nelly Nugrawati Nugrawati; Nur Ekawati (Jurnal LENTERA, 2026)
Nutritional problems remain a major public health challenge in Indonesia, particularly in rural areas, and contribute to the high risk of stunting among children under five. The utilization of locally available, nutrient-dense foods is one of the key strategies in family- and community-based stunting prevention. This community service activity aimed to improve the knowledge and skills of posyandu cadres, pregnant women, and mothers with toddlers in utilizing Moringa oleiferaleaves as a local superfood to improve family nutrition and prevent stunting in Tabo-Tabo Village, Pangkep Regency. The methods included initial coordination, participant identification and recruitment, knowledge pre-test, nutrition education, practical training on processing Moringa oleifera leaves, post-test, as well as monitoring and evaluation through cadre logbooks in 2 weeks. A total of 30 participants were involved, consisting of 12 posyandu cadres and 18 mothers with toddlers. The results showed an increase in participants’ knowledge, with the proportion of participants in the good knowledge category rising from 13% before the activity to 77% after the activity. Skills in processing Moringa oleiferaleaves also increased significantly, from 17% to 67% in the good category. Post-activity monitoring indicated that most participants had begun to routinely incorporate Moringa oleifera leaves into their daily family menus. This activity proved effective in improving family nutrition knowledge, skills, and practices through an applicable, affordable, and sustainable local food–based education and training approach, and has the potential to support community-level stunting prevention efforts.